Pelatihan Visualisasi Data Bagi Siswa SMKS Katolik Kefamenanu - Chrisinta, Debora; Simarmata, Justin Eduardo; Mone, Ferdinandus (UNIB Press, 2024)
The data visualization training program held at SMKS Katolik Kefamenanu was carried out based on the need for a better understanding in managing data, especially among students. This community service aims to provide a deeper understanding of data visualization and technology integration in education. The implementation method includes material preparation, hands-on training sessions, and prates and post-test evaluations. The service results showed a significant increase in students' understanding of data visualization concepts, increased skills in using Microsoft Excel, and increased student interest in data analysis. Students also successfully apply the acquired skills in a practical context.